PENGARUH TEKANAN MASUK DAN TEKANAN KELUAR TURBIN TERHADAP DAYA PENGGGERAK GENERATOR - Najamudin Najamudin (JURNAL TEKNIK MESIN, 2019)
The steam turbine is a prime mover that converts the vapor potential energy to kinetic energy and is subsequently converted to mechanical energy in the form of turbine shaft rotation. Turbine shaft, directly connected with the actuated mechanism, steam turbine can be used in various industrial fields or power plants. Generally, the steam turbine consists of a stationary part called a stator or turbine housing and a rotating part called a rotor. In the stator there is a nozzle, where the steam is exposed inside so that its speed rises. While on the rotor there are moving blades and discs that are the hilt of the moving blade. Because the shape of the motion blade is made curved in such a way that the change in vapor momentum flowing between the blades will cause a force acting on the blade curve so that it is pushed. This drive is subsequently transmitted by the disc and resulted in a spin on the turbine shaft. Power plants in Indonesia use generators to generate electricity. For that required the engine as a prime mover one of which is a steam turbine, to meet the above needs, then the problem is how to analyze the power generated steam turbine based on the influence of inlet pressure and turbine outlet pressure to generator generator power to fit Planning specifications of the turbine steam that can be used as a driving generator in a steam power plant.